Mental Education of Student Candidate’s Guardian During Pandemic Covid-19 (Gontor Submission Exam Case Studies) - Awaluddin Faj; Moh Ismail (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Coronavirus disease 2019 or COVID-19 becomes a pandemic in most countries in the world. This pandemic outbreak harms the physical and psychological health of individuals and society. It also affects educational institutions and boarding schools. This study aims to gain understanding, mental readiness, and awareness of the guardian of student candidates who want to register their children to boarding school without their accompaniment. This research uses a phenomenological approach analysis of the mental readiness of highly motivated guardian candidates to put their children in boarding school, especially in Darussalam Modern Islamic Boarding School Gontor, during the pandemic. In general, the understanding of boarding school, the mental readiness of parents in registering their children to Gontor, and the preparation of the admission committee for new students of Darussalam Modern Islamic Boarding School Gontor are highly influencing the succession of registration in this pandemic condition. The study results that the totality of parents’ belief in boarding school is the key to their mental readiness in releasing their children to study in the boarding school without any companion. Besides, the performance of the Gontor new student admission committee is agile in implementing health protocols following COVID-19 health procedures to welcome student candidates coming from all over the region.